Characterization of telomeres and telomerase from the single-celled eukaryote Giardia intestinalis - Uzlíková, Magdalena; Fulnečková, Jana; Weisz, Filip; Sýkorová, Eva; Nohýnková, Eva; Tůmová, Pavla (Molecular and biochemical parasitology, 2017)
The ends of linear chromosomes, telomeres, are most commonly maintained by the enzyme telomerase. Our study presents the characteristics of telomeres and telomerase from the single-celled parasitic eukaryote Giardia intestinalis. Using fluorescence in situ hybridization, we localized telomeres during all stages of the trophozoite cell cycle and demonstrated differences in the observed number of telomeric foci, indicating telomere clustering. The length of Giardia telomeres was determined in different cell lines derived from WB clinical isolate using terminal restriction fragment analysis and ranged from 0.5 to 2.5kb; moreover, a BAL-31 digestion experiment did not reveal any long interstitial telomeric sequences in the genome. Despite the absence of the specific T motif in the telomerase catalytic subunit, the presence of an active telomerase enzyme synthesising telomeric repeats in Giardia was proved by a Telomere repeat amplification protocol assay, and its localization in nuclei was determined by the expression of recombinant GiTERT. Except for the Giardia-type TAGGG telomeric repeat, Giardia telomerase was proved to synthesize in vitro also other repeat variants, TAAGG and TAAGGG. In summary, despite its unusual characteristics, including a structurally divergent but active telomerase, unique terminal sequences and relatively short telomeres, the present data support the view that the chromosomal termini in Giardia are maintained in a conservative manner that is common to other eukaryotes.
Keywords: Giardia; transport proteinů; Chromosomes; Humans; telomerasa; giardiáza; podjednotky proteinů; telomery; repetitivní sekvence nukleových kyselin; Protein Transport; Telomere Homeostasis; In Situ Hybridization, Fluorescence; Telomerase; TRAP assay; mitóza; lidé; Terminal restriction fragment; Enzyme Activation; Giardiasis; buněčné linie; homeostáza telomer; Telomere; Telomeres; Repetitive Sequences, Nucleic Acid; Giardia lamblia; Cell Line; hybridizace in situ fluorescenční; Protein Subunits; Mitosis; aktivace enzymů